A software framework for coping with heterogeneity in the shopfloor - Fernández-Madrigal, Juan-Antonio; Galindo, Cipriano; Cruz-Martín, Ana; González, Javier (Assembly automation, 2007)
The CIM framework pursues the integration of components in a manufacturing enterprise by means of computer systems. This, however, may be obstructed due to heterogeneity in the field: programmable controllers, robots, sensors and actuators, etc. in communications: different kinds of networks and/or field buses; and in the programming tools for all these devices. Thus a solution is needed to integrate heterogeneous software/hardware components in a well-defined and flexible fashion. This paper seeks to address these issues. This paper proposes a metalanguage, called H, and a set of tools that serve for designing, implementing, deploying, and debugging distributed heterogeneous software on the shopfloor. The metalanguange includes fault-tolerance and real-time mechanisms, among other features. The use of a framework that can integrate different software and hardware components enables the engineer to take advantage of the best features of each existing technology. The use of object-oriented techniques, concurrent and distributed programming, and the isolation of heterogeneous parts, have also important benefits in the reusability and optimality of the solutions.